Wave–current entry of an asymmetric wedge in 3DOF free motions. (June 2018) - Cheng, Yong; Ji, Chunyan; Oleg, Gaidai; Bai, Xu
Highlights: The slamming process of an asymmetric wedge entering waves in the presence of currents is investigation. A fully nonlinear HOBEM is used to solve the wave–current entry problem. Some auxiliary functions are introduced to decouple the mutual dependence of structure motions and fluid flow. The hydrodynamic behaviors are systematically discussed in the following current, zero current and opposing current, respectively. The effect of the physical parameters on wave entry in the presence of the opposing current is examined for a wedge hitting wave crest. Abstract: A time domain higher-order boundary element method (HOBEM) is developed to simulate the coupling process of a two-dimensional freely falling wedge entering obliquely waves in the presence of uniform currents. The wave–current-wedge slamming model is established in the stretched coordinate system, in which the velocity potential is decomposed as the potential induced by the current speed, the scattering potential and the incident potential at the initial stage. Some auxiliary functions are used to decouple the mutual dependence of structure motions with three degrees of freedom (3DOF) and fluid flow. The presented model is verified against the published first-order boundary element method (FOBEM) solutions for wedge entering calm water in free fall motion and wedge entering waves with the prescribed velocity in the absence of currents. Simulations and comparisons are then made for a wedge entering into waves in the following current, zero current and opposing current, respectively. Various parametric studies in the opposing current are performed for a wedge hitting wave crest vertically, obliquely and with initial rotational motion. Detailed results are provided through free surface elevation, pressure distribution, accelerations and velocities, and their physical implications are discussed.